Heterogeneity of antibody-secreting cells infiltrating autoimmune tissues - Giovannini, Diane; Belbezier, Aude; Baillet, Athan; Bouillet, Laurence; Kawano, Mitsuhiro; Dumestre-Perard, Chantal; Clavarino, Giovanna; Noble, Johan; Pers, Jacques-Olivier; Sturm, Nathalie; Huard, Bertrand (Frontiers in Immunology, 2023)
The humoral response is frequently dysfunctioning in autoimmunity with a frequent rise in total serum immunoglobulins, among which are found autoantibodies that may be pathogenic by themselves and/or propagate the inflammatory reaction. The infiltration of autoimmune tissues by antibody-secreting cells (ASCs) constitutes another dysfunction. The known high dependency of ASCs on the microenvironment to survive combined to the high diversity of infiltrated tissues implies that ASCs must adapt. Some tissues even within a single clinical autoimmune entity are devoid of infiltration. The latter means that either the tissue is not permissive or ASCs fail to adapt. The origin of infiltrated ASCs is also variable. Indeed, ASCs may be commonly generated in the secondary lymphoid organ draining the autoimmune tissue, and home at the inflammation site under the guidance of specific chemokines. Alternatively, ASCs may be generated locally, when ectopic germinal centers are formed in the autoimmune tissue. Alloimmune tissues with the example of kidney transplantation will also be discussed own to their high similarity with autoimmune tissues. It should also be noted that antibody production is not the only function of ASCs, since cells with regulatory functions have also been described. This article will review all the phenotypic variations indicative of tissue adaptation described so for at the level of ASC-infiltrating auto/alloimmune tissues. The aim is to potentially define tissue-specific molecular targets in ASCs to improve the specificity of future autoimmune treatments.